Hadith #3389 - Sunan Abi Dawud - Abdur Rahman bin Ishaq عبد الرحمن بن إسحاق بن عبد الله; Abu 'Ubaida bin Muhammad bin Yasir أبو عبيدة بن محمد بن عمار بن ياسر العنسي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Walid bin Abi al-Walid الوليد بن أبي الوليد عثمان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
I heard Ibn Umar say: We did not see any harm in sharecropping till I heard Rafi’ ibn Khadij say: The Messenger of Allah (ﷺ) has forbidden it. So I mentioned it to Tawus. He said: Ibn Abbas told me that the Messenger of Allah (ﷺ) had not forbidden it, but said: It is better for one of you to lend to his brother than to take a prescribed sum from him.
Grade: Sahih

Hadith #4770 - Sunan Abi Dawud - Abu 'Ubaida bin Muhammad bin Yasir أبو عبيدة بن محمد بن عمار بن ياسر العنسي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Sa'id bin Zayd; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Talha bin 'Abdullah طلحة بن عبد الله بن عوف الزهري (Sunan Abi Dawud)
This man with the crippled hand was on that day with us in the mosque. We would sit with him by day and by night, and he was a poor man. I saw him attending the meals of ‘Ali (ra) which he took with the people, and I clothed him with a cloak of mine. Abu Maryam said: The man with the crippled hand was called Nafi` Dhu al-Thadyah (Nafi`, man of nipple). He had in his hand something like a female breast with a nipple at it ends like the nipple of the female breast. If had some hair on it like th
Grade: Hasan